Effect of Green Marketing, Green Consumption Values and Green Marketing Approaches on Organic Purchase Intention: Evidence from the Manipur - Neiba, Neiba; Singh, N. Tejmani (International Review of Management and Marketing, 2024)
Using three theoretical lenses –the theory of consumption values (TCV), the stimulus-organism-response (SOR) model, and the theory of planned behavior (TPB) - this research intends to investigate the effect of green marketing (green advertisement and green word of mouth), green consumption values (functional value, social value and emotional value), and green marketing approaches (green organic product and eco-labeling) on organic purchase intention. A sample of 285 Manipur consumers was used to test the hypothesized relationship. The data were critically analyzed using SEM-based multivariate approach SPSS 26, AMOS 21, and conditional process modeling (Model 4). The findings suggest that green advertisement (GA), green word of mouth (GWOM), functional value (FV), emotional value (EV), green organic product (GOP), and eco-labeling (EL) influence organic purchase intentions significantly and positively. The data further reveal that consumer product attachment (CPA) and environmental consciousness (EC) have a significant influence on the relationship between green marketing (GA & GWOM), green consumption value (FV, SV, & EV), green marketing approaches (GOP & EL), and organic purchase intention. This study provides theoretical insight to researchers and academicians on organic purchasing. Also, it offers guidelines and suggestions to devise green marketing strategies for producers/retailers/marketers dealing with organic food products.